Data collection and use in the Icelandic fishing industry - Ari Ólafsson 1985- (2010)
Apart from geothermal and hydro-electric energy, Iceland boasts only one significant natural resource: the fish in the ocean. The country’s economy depends heavily on revenues generated by seafood exports and will continue to so for the foreseeable future. With customers increasingly demanding freshness and traceability, it is important as ever to experiment with innovative solutions. Most Icelandic fisheries already collect vasts amount of data, e.g. through electronic log-books. By converting this data into useable information, both long- and short-term decision making could be greatly eased. Furthermore, such information could present regulatory authorities with a powerful weapon to combat a built-in problem of the ITQ system, namely, at-sea discarding of fish. Að undanskilinni þeirri orku sem fæst úr jarðvarma og vatnsföllum, býr Ísland aðeins að einni raunverulegri náttúruauðlind; fiskimiðunum. Frá landnámi hefur þjóðin nýtt þau bæði til fæðuöflunar og sköpunar útflutningsverðmæta. Hlutfallslegt mikilvægi sjávarútvegsins í útflutningi er enn hátt, og eftir hremmingar síðustu ára er ljóst að svo verður um ókomin ár. Því er mikilvægt sem aldrei fyrr að viðhalda, og auka, arðsemi iðnaðarins. Til að mæta kröfum neytenda um ferskleika hráefnis og rekjanleika verður að gera ákvarðanatöku skilvirkari. Sjávarútvegsfyrirtæki safna nú þegar miklu magni gagna, t.d. gegnum afladagbækur, sem bjóða upp á mikla möguleika í þessum efnum. Með því að beita á þau aðferðum aðgerðagreiningar og tölfræði mætti auðvelda alla ákvarðanatöku til muna. Í gagnaathugun gæti einnig leynst öflugt vopn gegn óhjákvæmilegum fylgifiski kvótakerfisins, brottkasti.